The Third Reich : politics and propaganda - Welch, David 1950- (Routledge, 1995)
1. The Conquest of the Masses -- 2. Goebbels as Propagandist -- 3. Restructuring the Means of Communication. The Ministry for Popular Enlightenment and Propaganda. The Reich Chamber of Culture. Radio. Press. Film -- 4. Propaganda and Public Opinion, 1933-9. The 'National Community' (Volksgemeinschaft). The need for racial purity. Charismatic leadership and the 'Hitler Myth' -- 5. Nazi Propaganda at War, 1939-45. Blitzkrieg and victory. The Russian campaign. Total war and the need for strengthening morale. Retreat into mythology and promises of retaliation -- Postscript: Germany's search for a bearable past. The Historikerstreit